PELATIHAN KADER LANSIA DAN PEMBENTUKAN PEER GROUP DISCUSSION “PENCEGAHAN DIABETES MELLITUS PADA LANSIA” DI BANJAR BATUCULUNG, KEROBOKAN - IGAA Sherlyna Prihandhani; Putu Widiastuti; Made Oktaviani Bulan Trisna (Synergy and Society Service, 2023)
Diabetes mellitus is often asymptomatic (asymptomatic), thus less motivating a person to seek treatment, and often the signs of such symptoms are ignored and believe that there is no problem with high blood pressure. The participation of cadres in controlling diabetes mellitus, especially in terms of improving health and driving healthy living behavior, is very necessary, so that the severity and risk of diabetes mellitus do not occur. Establishment of Peer Group Discussion "Diabetes Mellitus Prevention in the Elderly" in Banjar Batuculung, Kerobokan. This program offers three sessions with lecture methods, peer group discussion and also posters that will be implemented face-to-face. The material to be given includes understanding, signs of symptoms, complications and prevention of diabetes mellitus.